2002
DOI: 10.1002/ijc.10797
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of lung metastasis of mouse Lewis lung cancer P29 with transfection of the ganglioside GM2/GD2 synthase gene

Abstract: Ganglioside functions in tumor metastasis were analyzed by carbohydrate remodeling of a mouse Lewis lung cancer (subline P29) by introducing ␤1,4GalNAc-T cDNA. Although P29 was originally a low-metastatic subline in the s.c. injection system, it showed high potential in lung metastasis when i.v.-injected via the tail vein. Two lines of GM 2 ؉ transfectants showed markedly reduced metastatic potential to the lung compared to 2 control lines. However, cell proliferation rates and expression levels of various cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Also, Hakomori (37) proposed interactions between ganglioside and integrin as one of patterns for signal regulation in the membrane microdomain on the cell surface. We have also suggested the possibility that ganglioside GM2 modulates integrin function (47). Simultaneously, GD3 might also interact with unidentified growth factor receptor(s) and enhance the receptor function, as we demonstrated in the study of a rat pheochromocytoma cell line, PC12 (48).…”
Section: Discussionmentioning
confidence: 61%
“…Also, Hakomori (37) proposed interactions between ganglioside and integrin as one of patterns for signal regulation in the membrane microdomain on the cell surface. We have also suggested the possibility that ganglioside GM2 modulates integrin function (47). Simultaneously, GD3 might also interact with unidentified growth factor receptor(s) and enhance the receptor function, as we demonstrated in the study of a rat pheochromocytoma cell line, PC12 (48).…”
Section: Discussionmentioning
confidence: 61%
“…Several studies on the modulation of integrins by gangliosides have been reported. For example, membrane cholesterol and sphingolipids have been shown to modify the function of adhesion molecules present on the membrane (25,26). Gangliosides extracted from neuroblastoma cells or atherosclerotic plaques enhance platelet adhesion via integrin binding to collagen (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…These microdomains are referred to as lipid rafts or GEM/rafts, and have been considered to be involved in signal transduction, because a variety of signaling molecules, such as Src-family kinases and trimeric G proteins, are also physically associated with the microdomains (48). Moreover, a number of studies have been reported concerning the association of integrins and GEM/rafts (26). For example, the glycosylphosphatidylinositolanchored protein CD24 as a marker for poor prognosis of carcinomas (ovary, breast, and pancreas), induced localization of integrin ␤1 to GEM/rafts with its transfection into A125 and MDA-MB-435S cell lines (49).…”
Section: Discussionmentioning
confidence: 99%
“…These cells are characterized by short doubling times in vitro and in vivo and aggressive biological behavior. They can be propagated in wild-type C57B/6 mice, giving rise to lung adenocarcinomas (16)(17)(18). In these studies, we have developed and characterized a new murine model of MPE after instillation of lung adenocarcinoma cells in the pleural space of immunocompetent mice.…”
mentioning
confidence: 99%